Health care workers' recommendations for strengthening tuberculosis infection control in the Dominican Republic - Helena J. Chapman; Bienvenido A. Veras-Estévez; Jamie L. Pomeranz; Eddy N. Pérez-Then; Belkys Marcelino; Michael Lauzardo (Pan American Health Organization, 2018)
Objective. To describe health care workers' practical recommendations for strengthening adherence to Mycobacterium tuberculosis infection control practices in their health institutions and elsewhere across the Dominican Republic. Methods. In this qualitative study, 10 focus groups, with a total of 40 clinicians (24 physicians, 16 nurses), were conducted in 2016 at two tertiary-level institutions in the Dominican Republic. Grounded theory guided the analysis to expand on health care workers' recommendations for empowering clinicians to adhere to M. tuberculosis infection control practices. To ensure reliability and validity, the authors analyzed data and incorporated both peer debriefing with qualitative experts and participant feedback or validation on the final themes. Results. Six emerging themes were described: 1) education and training; 2) administrative policy; 3) infrastructure policy; 4) economic allocations; 5) research; and 6) public health policy. Conclusions. Future efforts may combine the health care workers' recommendations with evidence-based strategies in M. tuberculosis infection control in low-resource settings. This could pave the way for interventions that empower health care workers in their application of M. tuberculosis infection control measures in clinical practice.